ANALISIS PERILAKU DAN STRATEGI PENGELOLAAN RISIKO PETANI CABAI MERAH PADA LAHAN KERING DATARAN TINGGI DI JAWA TENGAH - Daryanto, Arief; Daryanto, Heny K; Kuntjoro, .; Saptana, . (Lampung University)
Farmersâ behavior is various in dealing with risks and their coping strategy. This paper aims to analyze farmersâ behavior in dealing with risks and management strategy of red pepper farm management in upland areas of Central Java. The study was conducted on February to March, 2009, on the red pepper producing centers at Selo sub district, Boyolali district and Karangreja sub district, Purbalingga district. Farmers adopted red pepper in their cropping patterns as a high economic value commodity and high-risk crop was classified as an ex ante risk management strategy. On the other hand, an interactive risk management was carried out through over using of fertilizers, pesticides, and labor. If the farms failed which caused by lower householdsâ incomes and farm sustainability, the farmers tended to use off-farm incomes to draw savings, to sell some assets, and to borrow as the ex post risk strategy management. The implications of the study are: (i) cropping patterns should include red pepper due to its significant contribution to their incomes; (ii) hybrid red pepper should be tolerant to various environment conditions and pestsâ attack; (iii) farm practice should be locally specific for upland areas; and (iv) lessening farmsâ risks through crop diversification agribusiness insurance.Â Â Farmersâ collaboration through farmersâ groups, contact farming, and revitalization of Agribusiness sub Terminals can be implemented to reduce red pepper marketing risks.